2011
DOI: 10.1007/s00535-011-0484-9
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3β inhibition sensitizes pancreatic cancer cells to gemcitabine

Abstract: The results indicate that GSK3β inhibition sensitizes pancreatic cancer cells to gemcitabine with altered expression of genes involved in DNA repair. This study provides insight into the molecular mechanism of gemcitabine resistance and thus a new strategy for pancreatic cancer chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 46 publications
6
54
0
Order By: Relevance
“…A number of in vivo studies have investigated the antitumor activity of distinct GSK-3 inhibitors in a variety of cancer cell line-derived tumor xenograft models [14,21,22,24,33,39,40]. These studies utilized toolkit GSK-3 inhibitors as monotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vivo studies have investigated the antitumor activity of distinct GSK-3 inhibitors in a variety of cancer cell line-derived tumor xenograft models [14,21,22,24,33,39,40]. These studies utilized toolkit GSK-3 inhibitors as monotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have found that GSK3β inhibition reduces cell proliferation, increases cell apoptosis and sensitizes cells to death by different stimuli (Table 1) [26,38,39]. These phenotypes resulting from GSK3β inhibition are attributable to a variety of mechanisms including disruption of NF-κB-mediated survival [26,40] activation of tumor suppressors (p53 and Rb) [41], increased expression of the proapoptotic factor Bim [42], and inhibition of human telomerase reverse transcriptase and telomerase [35].…”
Section: Introductionmentioning
confidence: 99%
“…GSK3β inhibition by the small molecule AR-A014418 sensitized pancreatic cancer cells to apoptosis induced by TRAIL (tumor necrosis factor-related apoptosis inducing ligand) both in vitro and in tumor xenografts [38]. In addition, AR-A014418 was shown to sensitize the Panc-1 pancreatic cell line model to gemcitabine both in vitro and in vivo [36,39]. The role of GSK3β in chemotherapy resistance, however, is controversial, as Mamaghani et al [43] reported an overall lack of synergy and in some cases even antagonism between GSK3β inhibition (by AR-A014418) and gemcitabine in a panel of 6 pancreatic cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of combination of AR-A014418 and gemcitabine were determined to be synergistic. One of the genes implicated in the response was the altered expression of p53-induced nuclear protein 1 which is a gene involved in regulating cell death and DNA repair(Shimasaki et al, 2012).The GSK-3 inhibitor lithium induces the ubiquitin-dependent proteasomal degradation of the downstream component of the HH signaling pathway glioma-associated oncogene homologue (GLI1). Lithium induced apoptosis and suppressed the tumorigenic potential of pancreatic cancer cells.…”
mentioning
confidence: 99%